If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5 + c) = 4(c + -3) (5 * 5 + c * 5) = 4(c + -3) (25 + 5c) = 4(c + -3) Reorder the terms: 25 + 5c = 4(-3 + c) 25 + 5c = (-3 * 4 + c * 4) 25 + 5c = (-12 + 4c) Solving 25 + 5c = -12 + 4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4c' to each side of the equation. 25 + 5c + -4c = -12 + 4c + -4c Combine like terms: 5c + -4c = 1c 25 + 1c = -12 + 4c + -4c Combine like terms: 4c + -4c = 0 25 + 1c = -12 + 0 25 + 1c = -12 Add '-25' to each side of the equation. 25 + -25 + 1c = -12 + -25 Combine like terms: 25 + -25 = 0 0 + 1c = -12 + -25 1c = -12 + -25 Combine like terms: -12 + -25 = -37 1c = -37 Divide each side by '1'. c = -37 Simplifying c = -37
| -3x-2(-6+6x)=(x+2) | | 2+5*(x+2)=7x+1 | | y-25=-7 | | 6x+4=3+19 | | 19-(x+8)=8x-7 | | 15-2000=17+2x | | 3(5y+2)-5=2(y-3) | | x+6x+11=39+3x | | 18+6(z-3)=5z | | 6(7-7x)+6(x+7)=12 | | 15+2000=17+2x | | 6p^2-11pj-10j^2=0 | | 2p+2=-18 | | 6-2(x-8)=24 | | 1/2(x-2)=5(x+6) | | .3x+1.8=.4(x+5)+.2 | | 5+9x=3+2*(x-1) | | .3x+1.8=.4(x+5)+2 | | 4(x+7)=3(x-8)+8 | | -5x-19=21-9x | | -5=x-8+7 | | 10x-2=45x+26 | | 15x+2000=17+x | | 8(3d-2)=-12.32 | | -6x+8=-17-x | | 9=3(s+2) | | 15=-5n+8n | | 15+2000x=17+x | | 3r^2+rs-10s^2=0 | | 5-11=z/-8 | | 6+(x/4)=-1 | | x+61=54 |